Breast cancer metastasis through the lympho-vascular system - Nathanson, S. David; Krag, David; Kuerer, Henry M.; Newman, Lisa A.; Brown, Markus; Kerjaschki, Dontscho; Pereira, Ethel R.; Padera, Timothy P. (Clinical & experimental metastasis, 2018)
Breast cancer metastasizes through the lymphovascular system to the regional lymph nodes in the axilla and to both visceral and non-visceral sites. Renewed interest in the route by which tumor cells gain access to blood and lymphatic capillaries are the subject of research at mechanical, anatomic, pathologic, genetic, epidemiologic and molecular levels. Two papers presented at the 7th International Symposium on Cancer Metastasis in San Francisco showed tumor cells entering the systemic circulation through the sentinel lymph node. This information challenges the current paradigm where clinicians believe that access is gained through intra- and peri-tumoral blood vessels and that metastasis to axillary lymph nodes is an interesting epi-phenomenon. The sentinel lymph node era has changed the modern surgical approach to the axilla and the basis of this change is summarized in this paper. A new approach to the management of axillary metastases after systemic therapy relies on determining whether there is a complete pathologic response; if no tumor is found in the previously biopsied node, a complete axillary lymph node dissection may be avoided. African American women seem to inherit a trait from West African ancestors and tend to develop more lethal types of breast cancer. These tumors may have a molecular machinery that enhances their ability to metastasize to visceral sites and future research may unearth the mechanisms for this phenomenon.